Household Income, Debt Service Ratio, and Early Childhood Education Participation in Indonesia - Imelda Regina Sumayku; Elvis Sumanti (Advances in Economics & Financial Studies, 2026)
Purpose: This study examines the relationship between household financial conditions and children’s participation in Early Childhood Education (ECE) institutions in Indonesia, focusing on household income and Debt Service Ratio (DSR). Research Method: This study employs a quantitative approach using secondary data from the Indonesia Family Life Survey (IFLS-5) conducted in 2014–2015 across 13 provinces. The final sample consists of 775 household observations. Preschool participation is measured as a binary variable covering ECE, kindergarten, and playgroup participation. The analysis applies Binary Logistic Regression using Maximum Likelihood Estimation (MLE). Results and Discussion: The findings show that household income is positively associated with preschool participation across all models. DSR also shows statistically significant associations across several specifications, although the relationship should be interpreted with caution, as DSR reflects only the household debt repayment burden. Stronger associations are identified in regency areas than in municipalities. Implications: The study highlights the importance of improving household economic resilience and equitable access to preschools. Originality: This study integrates the household debt repayment burden into the analysis of preschool participation using Indonesian household-level survey data.